2011
DOI: 10.1097/brs.0b013e3181fef890
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Association Between Low Back Pain and Paraspinal Muscle Atrophy Using Opposed-Phase Magnetic Resonance Imaging

Abstract: Low back symptoms and functional limitations over a 3-year period were not associated with increased fat content or a reduction in the cross-sectional area of lumbar paraspinal muscles among young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 28 publications
6
64
1
5
Order By: Relevance
“…In addition, due to the range of MFI quantification methods, MFI intra-and inter-rater reliability findings may not be easily compared across studies. Using opposedphase MRI, intra-rater reliability of lumbar multifidus and erector spinae MFI was found to be high in patients with persistent low back pain, with an ICC range of 0.86 to 0.88 (5). This study also found an equally high inter-rater reliability (ICC 0.85 -0.87) for MFI in these muscles.…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…In addition, due to the range of MFI quantification methods, MFI intra-and inter-rater reliability findings may not be easily compared across studies. Using opposedphase MRI, intra-rater reliability of lumbar multifidus and erector spinae MFI was found to be high in patients with persistent low back pain, with an ICC range of 0.86 to 0.88 (5). This study also found an equally high inter-rater reliability (ICC 0.85 -0.87) for MFI in these muscles.…”
Section: Introductionsupporting
confidence: 51%
“…Accordingly, the high inter-rater findings from the present study cannot be compared. Equally, due to a lack of reports on MFI inter-rater reliability, comparisons from the present study to existing literature is very limited; however, a high inter-rater reliability (ICC 0.85 -0.87) for MFI in M and ES muscles using opposed-phase MRI has been shown (5). These values are similar to the findings in the present study for M and ES MFI (M 0.83-0.88; ES 0.96) although a different fat quantification method was used in the present study.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations